2005
DOI: 10.1111/j.1365-2672.2005.02619.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular injuries upon exposure of Escherichia coli and Lactobacillus rhamnosus to high-intensity ultrasound

Abstract: Aims: To examine cellular injuries occurring in cells of Escherichia coli (Gram-negative bacteria) and Lactobacillus rhamnosus (Gram-positive bacteria) in response to a high-intensity ultrasound treatment using classical plate count technique and flow cytometry. Method and Results: According to plate count results, E. coli (D-value 8AE3 min) was far more sensitive than L. rhamnosus (D-value 18AE1 min) in their response to the ultrasound intensity applied (20 kHz, 17AE6 W). The dye precursor carboxyfluorescein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(44 citation statements)
references
References 28 publications
(28 reference statements)
1
40
0
2
Order By: Relevance
“…Given the existence of the outer membrane, no considerable changes in the PI-positive population were observed at first for E. coli compared to S. aureus, indicating that the E. coli cytoplasmic membrane was not severely affected under those circumstances. This phenomenon was in agreement with a published study (13) proving that under certain processing conditions, ultrasound could be selective, merely destabilizing the E. coli outer membrane without rupturing the cytoplasmic membrane. Thus, the outer membrane of an E. coli cell is an important target site for ultrasound treatment.…”
Section: Enumeration Of Surviving Cells By Plate Counts (Cultivability)supporting
confidence: 81%
See 1 more Smart Citation
“…Given the existence of the outer membrane, no considerable changes in the PI-positive population were observed at first for E. coli compared to S. aureus, indicating that the E. coli cytoplasmic membrane was not severely affected under those circumstances. This phenomenon was in agreement with a published study (13) proving that under certain processing conditions, ultrasound could be selective, merely destabilizing the E. coli outer membrane without rupturing the cytoplasmic membrane. Thus, the outer membrane of an E. coli cell is an important target site for ultrasound treatment.…”
Section: Enumeration Of Surviving Cells By Plate Counts (Cultivability)supporting
confidence: 81%
“…Most researchers have argued that the primary target of ultrasound is the cytoplasmic membrane, which consists of lipoprotein layers (11,12). Ananta et al, on the other hand, suggested that ultrasound-induced cell death might not be related to cytoplasmic membrane damage (13).…”
mentioning
confidence: 99%
“…Our current work strengthens the hypothesis that ultrasound creates holes or perturbations in the outer membrane lipid bilayer sufficiently large for the passage of relatively large hydrophilic compounds, including antibiotics. A more recent publication investigating the ultrasonic-enhanced permeability of E. coli and Lactobacillus rhamnosus toward fluorescent dyes also supported the hypothesis that transient holes in cell membranes are formed (Ananta et al, 2005).…”
mentioning
confidence: 73%
“…Ananta and colleagues (32), found primarily the OM of E. coli affected by ultrasound when certain processing conditions (i.e., continuous removing of the resulting heat) were applied. E. coli cells with an intact OM and stained with cFDA showed only weak green fluorescence, whereas ultrasound treated cells presented an increased fluorescent intensity.…”
Section: Fluorogenic Substratesmentioning
confidence: 99%